Cross-sectional study of partners’ tobacco consumption during their spouse’s pregnancy - Frédéric Fortin; Coralie Verrez; Thomas Hacquart; Bruno Pereira; Catherine Laporte (European Journal of General Practice)
Background A smoking partner is a major risk factor for passive smoking and continued maternal smoking.Objective To assess the smoking habits, knowledge, and information received to stop smoking of smoking partners during their spouse’s pregnancy.Method This was a cross-sectional study of partners who smoked at the start of pregnancy and whose spouses had just given birth. Recruitment was carried out in maternity hospitals in the Auvergne-Rhône-Alpes region from June 2021 to December 2021. Data were collected using a self-administered questionnaire.Results A total of 105 men using tobacco were recruited, average age 34 years (± 6.4). Of these, 46 (44%) had modified their consumption during pregnancy: 11 (10.5%) had stopped smoking until maternity hospital entry, 24 (23%) had cut down and 11 (10.5%) had relapsed after initial total cessation. A multivariate analysis revealed a statistically significant relationship between men’s change in smoking behaviour during pregnancy and a first pregnancy, an overweight participant, not living in a rural area, and information provided by the General Practitioner (GP). GPs are the first point of contact for participants looking for help to quit smoking. Among men who have not changed their smoking habits, 46% have not received any information from health professionals.Conclusions Intervention and medical information provided by GPs to smoking partners may be associated with changes in smoking habits during pregnancy. Additional prospective, comparative studies are needed to support a robust conclusion.